2003
DOI: 10.1080/0269905031000110409
|View full text |Cite
|
Sign up to set email alerts
|

Brain injury case management: the potential and limitations of late-stage intervention--a pilot study

Abstract: The focus of this study was to be upon case management intervention with the longer-term, often insidious cognitive and behavioural problems of brain injured patients, to effect a cohesive response towards improvement of function and social/community reintegration. Ten 'in depth' case management studies were developed. Age, sex, cause of injury, time post-injury, nature of brain injury,sequelae-and consequent intervention-differed widely. Three studies are précised in this paper. There was no attempt to match … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…In 2004, Fitzsimmons reported on 51 case studies with case management intervention for persons with TBI, acknowledging brain injury case management as a “comparatively new discipline” ( Fitzsimmons, 2003 , p. 947). The lack of homogeneity with definitions also creates a problem ( Quinn et al, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2004, Fitzsimmons reported on 51 case studies with case management intervention for persons with TBI, acknowledging brain injury case management as a “comparatively new discipline” ( Fitzsimmons, 2003 , p. 947). The lack of homogeneity with definitions also creates a problem ( Quinn et al, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…In 2014 the Public Health Agency of Canada reported that, based on current data, the number of hospitalizations for TBI in Canada will increase 28% by 2031. Case Management (CM) has emerged as a significant health service over the past two decades ( Applebaum & White, 2000 ; Fitzsimmons, 2003 ; Quinn, Pannone, Gruman & Roja, 2004 ), as has the sub-specialty of Life Care Planning ( Masel & DeWitt, 2010 ; Deutsch & Sawyer, 1985 ; Klinger, Baptiste & Adams, 2004 ). In 2009 National Standards of Practice were identified in Canada, and CM was defined as “ ... a collaborative, client-driven process for the provision of quality health and support services through the effective and efficient use of resources.…”
Section: Introductionmentioning
confidence: 99%
“…Ratings ranged from 0 out of 7 (41,42) indicating low methodological quality to 6 out of 7 indicating high quality (43). The majority of studies had clear research questions and appropriate methods of data collection, however some failed to clearly disclose these (40,41,42,44,45,46,47,48,49,50). Common methodological issues included poor reporting of methods of data collection and analysis, which resulted in these elements of included studies being assessed as 'can't tell' (e.g.…”
Section: Quality Appraisalmentioning
confidence: 99%
“…[Table 5 here] [Table 6 here] [Table 7 here] Measuring success in case management research and practice Six of the included studies reported on the challenges of measuring and evaluating the impact of case management for brain injury (14,15,16,28,48,49). Included reviews which explored the literature on the impact of case management on brain injury, concluded that there was no clear evidence on the effectiveness or ineffectiveness of case management for brain injury (14,15,16,49). This lack of evidence was deemed to be a result of a number of factors.…”
Section: Quality Appraisalmentioning
confidence: 99%
See 1 more Smart Citation